KEARIFAN LOKAL DALAM PENATAAN RUANG KAWASAN BENCANA VULKANIK STUDI KASUS: DESA KEPUHARJO CANGKRINGAN - Catharina Dwi Astuti Depari (TATALOKA, 2015)
Some successful disaster management especially in East Asia have demonstrated how the local wisdom could contribute to increasing the resilience of its communities toward disaster impacts. A new approach integrating local wisdom with modern science is now continuously developed and,  for this reason, a bottom up approach in which community’s aspirations accommodated must be well-considered. In design context, spatial ordering system could symbolize local values in which inherited knowledge towards disaster mitigation is embed. In terms of Merapi’s disaster prone-areas, the communities of Kepuharjo Village have inherited knowledge to coping with volcanic impacts that mostly expressed through their traditions and rites. The research aims to emphasize local wisdom as an essential element that contributes to increasing the community’s resilience towards volcanic impacts.  By investigating the types of local wisdom still existed and understood by the local citizens, and revealing the implementation of those values into the local’s urban structure. The research employs interpretive, and ethnography approaches in which interpretations based on local community’s experience and researcher’s knowledge towards the research focus establishedAbstract: Some successful disaster management especially in East Asia have demonstrated how the local wisdom could contribute to increasing the resilience of its communities toward disaster impacts. A new approach integrating local wisdom with modern science is now continuously developed and,  for this reason, a bottom up approach in which community’s aspirations accommodated must be well-considered. In design context, spatial ordering system could symbolize local values in which inherited knowledge towards disaster mitigation is embed. In terms of Merapi’s disaster prone-areas, the communities of Kepuharjo Village have inherited knowledge to coping with volcanic impacts that mostly expressed through their traditions and rites. The research aims to emphasize local wisdom as an essential element that contributes to increasing the community’s resilience towards volcanic impacts.  By investigating the types of local wisdom still existed and understood by the local citizens, and revealing the implementation of those values into the local’s urban structure. The research employs interpretive, and ethnography approaches in which interpretations based on local community’s experience and researcher’s knowledge towards the research focus established